The Significant Role of the Microfilament System in Tumors - Jiang, Xin; Qin, Yiming; Kun, Liu; Zhou, Yanhong (Frontiers in Oncology, 2021)
Actin is the structural protein of microfilaments, and it usually exists in two forms: monomer and polymer. Among them, monomer actin is a spherical molecule composed of a polypeptide chain, also known as spherical actin. The function of actin polymers is to produce actin filaments, so it is also called fibroactin. The actin cytoskeleton is considered to be an important subcellular filament system. It interacts with numerous relevant proteins and regulatory cells, regulating basic functions, from cell division and muscle contraction to cell movement and ensuring tissue integrity. The dynamic reorganization of the actin cytoskeleton has immense influence on the progression and metastasis of cancer as well. This paper explores the significance of the microfilament network, the dynamic changes of its structure and function in the presence of a tumor, the formation process around the actin system, and the relevant proteins that may be target molecules for anticancer drugs so as to provide support and reference for interlinked cancer treatment research in the future.